LIABILITY FOR IMMATERIAL DAMAGE FOR THE BREACH OF THE MORAL RIGHTS ON INTELLECTUAL CREATIONS IN THE MACEDONIAN LAW - Zdraveva, Neda (The Association of Intellectuals “Democratic Club” – Skopje, 2021)
The right to intellectual property, as a subjective right, is most often associated with the economic rights arising form it - rights that provide the right holder with concrete and specific economic benefits from his work. Yet moral rights are those that ensure the close personal connection of the holder of the right to his intellectual creation. They are protected in different ways in the international instruments that regulate the Intellectual Property Law, as well as in the Law of the European Union. The Macedonian legislation contains a series of provisions that regulate those rights and determine the mechanisms for liability for immaterial damage due to their violation. In the paper, the moral rights of creators are considered precisely from these aspects.
Keywords: industrial property right, copyright, moral rights, immaterial damage, liability